The Implementation of Da'wah and Work Culture and Its Correlation in Increasing Work Productivity Within the Ministry of Religious Affairs of Majene Regency - Mustapa Tangngali; Muliaty Amin; Mahmuddin Mahmuddin; Firdaus Muhammad (PT Publikasiku Academic Solution, 2023)
This study aims to analyze the Implementation of Da'wah and Work Culture and its Correlation in Increasing Work Productivity within the Ministry of Religious Affairs of Majene Regency. Qualitative research with naturalistic type, data collection is carried out by observation, interview, and documentation. Primary data sources are obtained from employees of the Majen district gama ministry, secondary data from relevant articles. The results showed that the implementation of da'wah and work culture at the Majene Regency Ministry of Religious Affairs Office had been realized but the level of implementation was different between one work culture and another, on average the easiest work culture to implement was exemplary and what was considered difficult was innovation, it was also found that da'wah and work culture were correlated to increase the productivity of the work of stakeholders.